Contract Interpretation in Investment Treaty Arbitration A Theory of the Incidental Issue - Chernykh, Yuliya (International Litigation in Practice, 2022)
For the first time, a monograph provides a systematic, in-depth account of contract interpretation in investment treaty arbitration and offers a conceptual paradigm that would enhance the quality of the tribunals' reasoning.; Readership: The monograph is of relevance for legal scholars, practitioners and policymakers in the field of investment treaty arbitration. The book will also be of additional value to postgraduate and doctoral students.